HUBUNGAN TINGKAT PENGETAHUAN LITERASI POLITIK DENGAN KARAKTER DEMOKRASI SISWA DI SMA NEGERI 1 SABAK AUH - Anjar Ratna Sari; Ahmad Eddison; Hambali Hambali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract This research is motivated by the level of knowledge of political literacy and the character of Democracy in SMA Negeri 1 Sabak Auh, Siak Regency which is increasingly prominent in discourse and policies in the life of the world of education. The formulation of the problem in this research is how is the relationship between the level of knowledge of political literacy and the character of student democracy at SMA Negeri 1 Sabak Auh, Siak Regency. The purpose of this study was to determine how the relationship between the level of political literacy knowledge and the student's democratic character at SMA Negeri 1 Sabak Auh, Siak Regency. The practical benefit for researchers is to develop awareness with the world of education, so that they can be more enthusiastic in applying what they get in the world of education. The population of this study were all students of SMA Negeri 1 Sabak Auh, Siak Regency, totaling 217 students. The sample in this study was 54 students with the technique used, namely proportional sampling. Data collection methods are questionnaires, observations, interviews and documentation. Data processing with statistical analysis using the Pearson product moment coefficient formula assisted by the SPSS version 16 application, the hypothesis formulated is that there is a relationship between the level of political literacy knowledge and the student's democratic character at SMA Negeri 1 Sabak Auh, Siak Regency. Based on statistical test analysis using the Pearson product moment correlation coefficient, the character of Democracy at r-count is 0.476. While the r-table on the number of samples 54 is 0.279. In accordance with the provisions if r-count is greater than the value of r-table (0.476> 0.279) then Ho is rejected and Ha is accepted, thus there is a relationship between variable X or political literacy with variable Y or Democratic Character. The correlation or relationship between political literacy and the character of democracy is 47.6%, it is in the area of 0.41-0.60 with a moderate interpretation of the relationship, so the criteria for the strength of the relationship between the variables of political literacy and democratic character have a moderate relationship.Key Words: Relationship, Level of Knowledge, Political Literacy, Character, Democracy